Report on a complete chloroplast genome sequence of wild apple tree, Malus sieversii (Lebed.) M. Roem - Young-Ho Ha; Bagila Maisupova; Kyung Choi; Hyun-Jun Kim; Daniyar Dosmanvetov; Bulkair Mambetov; Ainur Utebekova; Dong-Kap Kim; Kae Sun Chang; Aleksey Kim; Soo-Rang Lee; Seung Hwan Oh (Mitochondrial DNA. Part B. Resources, 2020)
We report a complete chloroplast genome sequence of Malus sieversii. The CP genome was 160,223 bp in length with a typical quadripartite structure. Length of large single-copy (LSC) was 88,334 bp, whereas small single-copy (SSC) was 19,179 bp in length. A pair of inverted repeats (IR) were 26,355 bp. In total, 128 genes were found including 83 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. The phylogenetic analysis on concatenated data set retrieved from 78 protein-coding genes revealed that M. sieversii was closely related with both M. ×domestica and M. sylvestris.